The Lost Good Self: Why the whistleblower is hated and stigmatized. Issue 7 (July 2021) - Stein, Mark
In this paper I develop a new explanation that furthers our understanding of why whistleblowers are frequently hated and stigmatized. I call into question the implicit assumption in the literature that whistleblowers are hated and stigmatized exclusively because they represent the 'other'. Instead, I take a different view and argue that, especially where staff have a moral commitment to their work, whistleblowers may also be felt to be problematic because they unconsciously represent the lost good 'self' of staff members. I draw on Kleinian psychoanalytic ideas in developing theory, and use the crisis at the Mid Staffordshire National Health Service Trust in the UK as a contemporary case illustration. This paper contributes to the whistleblower literature as well as to the literature that applies psychoanalytic ideas to the study of management and organization, and it also identifies areas for future research.